Pengoptimalan Mangrove dalam upaya peningkatan kesejahteraan masyarakat Desa Pasar Rawa Kecamatan Gebang Kabupaten Langkat - Eka Umi Kalsum; Warsiman; Ervina Sari Sipahutar; Anjani Sipahutar; Nuraida; Andri Ramadhan; Prinsi Rigitta (LPPM Universitas Al-Azhar medan, 2024)
The preservation of mangrove forests must always be maintained, because mangrove forests have biological, ecological and economic functions which are of course very beneficial for the survival of every living creature. Optimal use of mangrove forests will bring many benefits to the lives of communities around the coast of Pasar Rawa. Success in mangrove management will improve the welfare of the community around the coast of Pasar Rawa. In implementing this program, the method of giving lectures about optimizing mangroves is used in an effort to improve the welfare of the people of Pasar Rawa. The aim of this program is for partners to be able to improve the welfare of the people of Pasar Rawa.